Design(er) leadership in large corporations - Santos, José Manuel Fernandes dos (2021)
Submitted by Susana Santos (susana.santos@universidadeeuropeia.pt) on 2021-05-27T17:42:15Z No. of bitstreams: 2 IADE-PhD_Dissertation_JosedosSantos_final18Dec2020.pdf: 19975706 bytes, checksum: a383085f49f125f4b1b852c6ab473e94 (MD5) PhD_Design_Jose_CAPA.pdf: 379969 bytes, checksum: a5dfe38ffd5ad10ed5179ae7744df70a (MD5)